Role of the adipose PPARγ-adiponectin axis in susceptibility to stress and depression/anxiety-related behaviors - Guo, M (Mol Psychiatry, 2017)
Adaptive responses to stressful stimuli involving behavioral, emotional and metabolic changes are orchestrated by the nervous and endocrine systems. Adipose tissue has been recognized as a highly active metabolic and endocrine organ, secreting adipokines that operate as hormones to mediate the crosstalk with other organs including the brain. The role of adipose tissue in sensing and responding to emotional stress and in behavioral regulation, however, remains largely unknown. The nuclear receptor peroxisome proliferator-activated receptor gamma (PPARγ) is a key transcriptional factor controlling adipokine gene expression. Here we show that chronic social defeat stress decreases messenger RNA and protein levels of PPARγ in adipose tissue of susceptible but not resilient mice, which was correlated with social avoidance behavior. A corresponding reduction in adipose adiponectin production was observed in susceptible mice. Rosiglitazone, a blood–brain barrier-impermeant PPARγ-selective agonist, elicited antidepressant- and anxiolytic-like behavioral effects in wild-type mice, with a concurrent increase in plasma adiponectin levels. These effects of rosiglitazone were absent in mice lacking adiponectin but having normal PPARγ expression in adipose tissue and brain. Moreover, pretreatment with the PPARγ-selective antagonist GW9662 blocked rosiglitazone-induced adiponectin expression and antidepressant/anxiolytic-like effects. Together, these results suggest that the behavioral responses to rosiglitazone are mediated through PPARγ-dependent induction of adiponectin. Our findings support an important role for the adipose PPARγ-adiponectin axis in susceptibility to stress and negative emotion-related behaviors. Selectively targeting PPARγ in adipose tissue may offer novel strategies for combating depression and anxiety.